Atypical aluminium patch tests in children with persistent itching postvaccinal nodules. Issue 4 (15th April 2018) - Raison‐Peyron, Nadia; Genillier‐Foin, Nathalie; Bessis, Didier; Milpied, Brigitte
Abstract: Persistent itching nodules related to aluminium‐adsorbed vaccines are well known in children with frequent positive patch tests to aluminium when tested. We report two cases of children with persistent postvaccination nodules who presented with atypical eruptions after aluminium patch tests.